Assessing the impact of nintedanib and pirfenidone on lung function in idiopathic pulmonary fibrosis: a comprehensive meta-analysis - Luan, Zhaoji; Muthal, Amol; Mohod, Smeeta (Vojnosanitetski pregled, 2026)
Background/Aim. The incidence of idiopathic pulmonary fibrosis (IPF) has been increasing each year. Although pirfenidone and nintedanib were approved in 2014, they received only conditional recommendations, and no medication has yet been strongly endorsed for IPF treatment. The aim of the study was to compare the safety and efficacy of pirfenidone and nintedanib. Methods. All randomized and non-randomized clinical trials were identified by searching databases for published studies, including Medline, Embase, Scopus, Google Scholar, and ClinicalTrials.gov. A meta-analysis was conducted to evaluate the impact of pirfenidone and nintedanib on clinical outcomes and safety. Patients treated with pirfenidone were compared with those treated with nintedanib. Results. This study included twelve papers. Both pirfenidone and nintedanib were found to significantly reduce the decline in mean forced vital capacity (FVC) and mean diffusion capacity of the lungs for carbon monoxide (DLco) at 6 and 12 months. No significant difference was observed between pirfenidone and nintedanib in terms of improvement in FVC or DLco. Similarly, both antifibrotic agents had similar safety profiles. However, patients receiving nintedanib experienced significantly fewer instances of diarrhea (p < 0.00001) compared to those receiving pirfenidone, whereas patients receiving pirfenidone experienced significantly fewer instances of skin rash (p < 0.00001) compared with those receiving nintedanib. Conclusion. Potential differences between pirfenidone and nintedanib can be inferred from the effectiveness ranking derived from this meta-analysis. Further direct comparative studies are necessary to explore this issue, which will help us better understand the potential of combinatorial, sequential, or adjunctive treatment regimens in which both antifibrotic agents might play a crucial role for a specific group of IPF patients.
Keywords: drug-related side effects and adverse reactions; drug therapy; idiopathic pulmonary fibrosis; nintedanib; pirfenidone; respiratory function test.